2017
DOI: 10.19082/4042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antimicrobial effects of titanium tetrafluoride, chlorhexidine, xylitol and sodium fluoride on streptococcus mutans: An in-vitro study

Abstract: IntroductionNo studies have yet documented the bactericidal effects of TiF4, and its role in the treatment of dental caries, and no definite protocol has been introduced to regulate its use. The aim of this study was to determine the antimicrobial/bactericidal effects of TiF4 on Streptococcus Mutans (S. Mutans) and to compare it with chlorhexidine (Chx), sodium fluoride (NaF) and xylitol.MethodsThis study was conducted at the Shiraz University of Medical Sciences microbiology laboratory during March 2015 to Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
3
0
3
Order By: Relevance
“…The antibacterial effect of xylitol have been evaluated by various studies [95,96], but the amount added to the materials may change the efficacy. According to a study, it was found that it did not show any antibacterial effect under a certain level [97]. The reason that Jack N’ Jill toothpaste did not exhibit any antibacterial activity in the present study may be due to its low xylitol content.…”
Section: Discussionmentioning
confidence: 57%
“…The antibacterial effect of xylitol have been evaluated by various studies [95,96], but the amount added to the materials may change the efficacy. According to a study, it was found that it did not show any antibacterial effect under a certain level [97]. The reason that Jack N’ Jill toothpaste did not exhibit any antibacterial activity in the present study may be due to its low xylitol content.…”
Section: Discussionmentioning
confidence: 57%
“…We expected that this layer would interfere in the microorganism adhesion and biofilm growth and activity; but we found no antimicrobial effect of TiF 4 varnish under this model. Recently, Eskandarian, et al 9 (2017) showed antimicrobial effect of TiF 4 , however, using a model and a fluoride preparation that are far to simulate the real conditions. They applied a planktonic model (broth dilution and disk diffusion) and neutralized TiF 4 solution to achieve a pH of 7.2, which is shown to negatively impact its effect on the tooth 29 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Outro estudo comparou xilitol com outras substâncias antimicrobianas e não verificou nenhum efeito do álcool sobre uma cepa de S. mutans. 21 Souza et al (2015) 19 avaliaram diferentes dentifrícios contra S. mutans e Candida albicans e verificaram halo de inibição nos dentifrícios contendo tanto xilitol associado ao fluoreto quanto xilitol associado ao triclosan. Evans et al (2015) 22 testaram diversos dentifrícios infantis e componentes como xilitol e triclosan em diferentes concentrações contra S. mutans, Streptococcus sanguinis e Lactobacillus acidophilus.…”
Section: Discussionunclassified
“…[11][12][13][14] Estudos laboratoriais in vitro em geral têm comprovado a eficácia do xilitol em cepas de S. mutans, 9,[15][16][17] no entanto, outros estudos somente verificam sua ação, quando associado a fluoretos ou outros agentes anitimicrobianos. [18][19][20][21][22] Portanto, o objetivo deste estudo foi avaliar a eficácia in vitro de um dentifrício não fluoretado (marca Orgânico Natural®) na inibição da cepa de S. mutans, um dos principais agentes etiológicos no processo da cárie dentária.…”
Section: Introductionunclassified